Additive manufacturing enables personalised porous high-density polyethylene surgical implant manufacturing with improved tissue and vascular ingrowth. (March 2021) - Paxton, Naomi C.; Dinoro, Jeremy; Ren, Jiongyu; Ross, Maureen T.; Daley, Ryan; Zhou, Renwu; Bazaka, Kateryna; Thompson, Robert G.; Yue, Zhilian; Beirne, Stephen; Harkin, Damien G.; Allenby, Mark C.; et al.
Highlights: Porous high-density polyethylene surgical implants are manufactured using selective laser sintering. Plasma treatment improves cell attachment in vitro and vascularisation in vivo. Control over scaffold porosity and surface properties improve tissue ingrowth. Abstract: Porous high-density polyethylene (pHDPE) surgical implants have played a significant role in aesthetic, reconstructive and skeletal augmentation procedures for more than 30 years and have been the gold-standard synthetic implant used in more than 400, 000 procedures worldwide. The effects of pHDPE implant properties such as porosity, geometry and surface chemistry are crucial considerations. Additive manufacturing and plasma surface treatment are promising approaches to induce rapid tissue integration and vascularisation, improve healing times and lead to more satisfactory patient outcomes. Here, a novel pHDPE scaffold architecture obtained by laser sintering was characterised to quantify porosity variations as a result of manufacturing, compared to scaffolds manufactured via traditional moulding, laser sintering, and the clinical gold-standard surgical implant, MEDPOR Ⓡ . Plasma surface treatment was also explored as a means of improving the hydrophilicity of the HDPE. An in vitro cell culture study examined the attachment of cells on treated and non-treated scaffolds. After 3 days, plasma-treated scaffolds exhibited a 1.6-fold increase in cell attachment compared to non-treated, hydrophobic samples. Plasma-treated and non-treated samples were then implanted subcutaneously in rats for 1, 4, and 8 weeks to assess biocompatibility, tissue ingrowth and vascularisation. Histological analysis revealed that laser sintered StarPore Ⓡ scaffolds exhibited significantly higher tissue ingrowth compared to the moulded scaffolds, whilst fibrous encapsulation dominated the tissue response in moulded StarPore Ⓡ scaffolds. Plasma treatment did not significantly affect the quantity of tissue ingrowth, however it significantly increased the density of blood vessels within sintered StarPore Ⓡ scaffolds by an average of 86.6%. Overall, this study demonstrated that novel manufacturing and plasma treatment of pHDPE surgical implants enhanced cell attachment in vitro and increased blood vessel density in laser sintered StarPore Ⓡ scaffolds in vivo . Graphical abstract: Image, graphical abstract